Optimal l-arginine dosage for pressure injury healing in home care settings: a six-month retrospective analysis - Chen, Nai-Ching; Pu, Lihui; Huang, Tai-Yang; Lin, Chia-Shu; Hung, Kuo-Chuan; Li, Yu-Yu (Frontiers in Public Health, 2025)
BackgroundPressure injuries present a significant challenge for patients receiving home care, particularly those with limited mobility. Although l-arginine supplementation has shown promise for wound healing, the optimal dosage remains unclear. This study compared the effectiveness of two daily l-arginine doses (7 g versus 14 g) in treating pressure injuries over a six-month period.MethodsWe retrospectively reviewed the medical records of 120 adult patients with grade 3 or 4 pressure injuries who received home care between June and December 2023. Patient wounds were evaluated using the DESIGN-R assessment tool, which measures various aspects of wound healing. Statistical analysis was performed using SPSS 26.0, employing generalized estimating equations (GEE) to account for repeated measurements over time.ResultsThe study found that patients receiving the 7 g daily l-arginine dose showed significantly better wound healing after 1 month compared to those receiving 14 g (p < 0.001). While healing rates varied throughout the study period, the 7 g dose consistently demonstrated superior outcomes by the six-month mark (p < 0.05). Notably, the higher 14 g dose did not provide additional healing benefits at any point during the study.ConclusionOur findings indicate that a daily 7 g l-arginine supplement effectively promotes both early- and late-stage healing of pressure injuries in home-care patients. This lower dose not only matches or exceeds the healing outcomes of the higher dose, but also presents a more cost-effective treatment option. Healthcare providers may consider implementing a 7 g dosage as a standard protocol for pressure injury treatment in home care settings.